An effective non-iterative “ λ-logic based” algorithm for economic dispatch of generators with cubic fuel cost function - Theerthamalai, Adhinarayanan; Maheswarapu, Sydulu (International journal of electrical power & energy systems, 2010)
This paper presents a very fast and effective non-iterative “ λ-logic based” algorithm for economic dispatch (ED) with cubic cost function of thermal units. Representation of generator fuel cost curves by polynomials in real-time economic dispatch is standard practice in the industry and it shows a great influence on the accuracy of the economic dispatch solution. As the proposed approach is a direct or non-iterative method, it does not demand any initial guess values for ED of units for given demand ( P D ). Many of the existing conventional methods fail to impose p-limits at violating units and find difficult in dealing with cubic cost function that reflect nonlinearity of the actual generator response. The proposed method is very efficient for both small and large size of generating units with cubic fuel cost function in the problem and it remarkably reduces the computation time. The proposed algorithm has been tested successfully on three units, five units and 26 units and results are reported in the paper.